Cases on quality teaching practices in higher education - Salter, Diane J., 1950-; Prosser, Michael, 1949- (USA INFO, 2013)
"This book presents individual approaches and institutional examples to benefit teachers at the individual level as well as institutional leaders involved in change"--Provided by publisher.
Includes bibliographical references and index.
Keywords: College teaching